Implementación de un sistema para la gestión deportiva de la liga barrial Eloy Alfaro mediante la utilización de api_rest y códigos qr - Ichina Tuapanta, Bryan Gustavo (2022)
The technological proposal was developed at Eloy Alfaro neighborhood soccer league of Latacunga canton, Cotopaxi province, with the objective to design and implement a system that facilitates organizational processes of championship carried out by the league. To develop this project, a methodology focused on incremental iterative development was used, which allowed to capture requirements and the implementation of the system, based on open-source tools such as Android Studio and ATOM, these use programming languages such as java, php, among others. On the other hand, an object-oriented database manager such as PostgreSQL was used. The research is based on the analysis of how different championships are developed, which do not have adequate planning or monitoring, taking data and results empirically without detail that helps to control the processes and data storage. The implementation of computer tools in the league, generates a better performance being able to manage different parameters that intervene on the organization of a sports championship, benefiting management staff that will be the ones who manage the championship, at this way the league information will be socialized in a better way with community, players and external people.